Betænkninger over Danmarks og Norgis Kirke-Ritual af 1685 fra Aalborg stifts geistelighed, 1735 - Skovmose, Kristian R. (Kirkehistoriske Samlinger, 1991)
The article presents and discusses a dossier of considerations on the official Danish book of rituals: »Danmarks og Norges Kirke-Ritual« of 1685, made in 1735 by members of the clergy of the diocese of Aalborg at the request of the King who -it can be reasonably assumed - wanted to pave the way for a reform, governed by the spirit of Pietism. The Aalborg clergy, however, were generally well satisfied with the existing ritual though a limited number of pietistically inclined members advocated minor changes with a view to ensure the sincerity of confession and strengthen the catechization of children.